A Study on Correlation of High-Sensitivity C-Reactive Protein and renal function in Patients With Type 2 Diabetes Mellitus in a tertiary care centre (Journal of Pharmaceutical Negative Results, 2023)
Background : Type 2 Diabetes mellitus can lead to many chronic complications, one of which is microvascular complications. In addition, approximately one in four patients with T2DM will have comorbid diabetic kidney disease (DKD) in the progression of T2DM. DKD is the most common cause of leading to end-stage renal disease worldwide and is a primary cause of mortality among patients with DM . Therefore, early intervention plays a vital role in preventing DKD development. To establish effective intervention strategies for DKD in clinical practice, identifying risk factors related to the presence of DKD is available. Objectives : To study the Correlation of High-Sensitivity C-Reactive Protein and renal function in Patients with Type 2 Diabetes Mellitus.Methodology : Cross sectional observational study done in General Medicine department of the Chettinad Health and Research Institute 2 months i.e December 2022 and January 2023. Patients who are known type 2 Diabetes Mellitus with Diabetic history of more than 5yrs were included.Results : A total of 100 diabetic patients were included in the study during the study period. Figure 2 shows that the among the 100 study population 36% of the diabetics showed microalbuminuria and 64% did not showed microalbuminuria. Study showed different parameters among the patients with microalbuminuria and without microalbuminuria. Mean age of the study population among the two groups, duration of diabetes, FBS levels, BMI, SBP, DBP levels showed significant difference among the two groups i.e p<0.05. HbA1C levels were more among the microalbuminuria patients (6.66± 1.00 v/s 6.44± 1.06) but it was not statistically significant.Among the serum proteins, serum albumin and total protein showed decreased levels among the microalbuminuria patients but the serum globulin levels were within the normal range among the two groups. The differences of serum albumin and total proteins were significant. Renal function tests showed blood urea levels were within the normal range among the two groups but the serum creatinine levels were significantly high among the microalbuminuria patients. 24 hours Urine albumin levels showed that higher value among the microalbuminuria patients compared to the other group. Urine casts were not present among the both groups. hsCRP levels were compared which showed significant differences among the two groups. The hsCRP levels also showed high levels of CRP with patients having diabetes for more than 10 years compared to patients with duration of diabetes between 5 to 10 years and the difference was statistically significant. the bio markers of the diabetes also showed significant increase in the group having the higher CRP levels.Conclusion : It has been concluded that higher levels of hs CRP can be a prognostic element for the development of DM. It also has positive correlation with HbA1c, reflecting the glycemic status of the patient. The study shows that the early monitoring of the hsCRP can help managing and identifying the development of the diabetic kidney disease and thus can be managed appropriately and timely to prevent the development of the complications.